A Multi-Group Structural Analysis of Digital Banking Adoption Determinants Across Generational Cohorts in Indonesia - Tribuana, Dhimas; Narimawati, Umi; Syafei, M. Yani (Pandawan, 2026)
This study investigates factors affecting Digital Banking Adoption (DBA) across generations in Indonesia, focusing on performance expectancy, effort expectancy, social influence, facilitating conditions, and trust. Employing a cross-sectional design, the study collected data through a structured questionnaire administered to 360 respondents, selected through purposive and clustering sampling, from major cities including Jakarta, Bandung, Surabaya, and others. Structural Equation Modelling (SEM) and Multi-Group Analysis were applied to test hypotheses and assess generational differences in DBA. Findings reveal that performance expectancy, facilitating conditions, and trust significantly influence DBA, with notable differences across generations: Baby Boomers prioritize facilitating conditions, Generation X emphasizes performance expectancy, and Generation Y values both performance and effort expectancy. Generation Z, despite being tech-savvy, benefits from enhanced support structures for improved banking experiences. These results highlight the importance of tailored, generation-specific strategies in digital banking, providing valuable insights for service providers aiming to enhance user experience and adoption across demographic groups.